The Bibliometric Analysis of Forensic Nursing and Midwifery - Dilek Ocalan; Acar Bektas, Hatice; Uysal, Serdar; Özgür Alparslan (KHD-Production, 2023)
As the first responders to forensic cases, nurses and midwifes have vital roles in conducting initial interview, physical examination, collecting and recording evidence and maintaining chain of custody. This study aims to map out the evolution of the fields of forensic nursing and forensic midwifery by focusing on the trend topics, the most active journals, top cited authors and publications, author productivity, productive organizations, journals, and countries of collaboration through bibliometric approach. To achieve this aim, we reviewed article title, abstract and keyword categories of Scopus Database using the phrase, «forensic» and «nursing» or «midwifery» and found a total of 2243 publications for the years between 1972 and 2022. As the midwifery publications in the literature are indexed within the «nursing» field, we restricted the research to «nursing» field and found 1385 publications. After removing duplications, we analyzed 1332 research and conducted visualization through ‘VosViewer’ and ‘R biblioshiny’ programmes. Best to our knowledge, this is the first bibliometric analysis which contributes to the related literature and to forensic scientists.